Ranking of sustainability in the environmental model of Sangan Ore Complex - Mehran Baettela; Saeed Karimi; Hamidreza Jafari (Entorno Geografico)
The mining area belongs to the ecologically fragile area, whose ecological and environmental problems have aroused the concern of researchers, for this purpose, studies are conducted in the field of environmental quality, sustainability and vulnerability of the ecosystem, ecological civilization and ecological security. To select the most appropriate indicators for the development of Sangan iron ore mines, sustainable development indicators from the main set of indicators of the Sustainable Development Commission were used. The FARE technique is based on the relationship between system parameters, that is, the direction and strength of their influence. Direction is indicated by a positive or negative, indicating that the considered criterion either affects or depends on another criterion. This technique was used to evaluate environmental indicators of mines. The results show that according to the opinion of experts, in the economic dimension, the share of women in direct paid employment in the mining sector has the highest weight and the income of farmers has the lowest weight. In the social dimension, the immigration rate has the highest weight and the dependency rate has the lowest weight. In the environmental dimension, Water quality has the highest weight and endangered species has the lowest weight.